MiR-490-3p Silences CDK1 and Inhibits the Proliferation of Colon Cancer Through an LLPS-Dependent miRISC System - Qin, Da; Wei, Rui; Zhu, Shengtao; Min, Li; Zhang, Shutian (Frontiers in Molecular Biosciences, 2021)
Liquid-liquid phase separation (LLPS) is a burgeoning concept in cell biology, which was associated with miRISC machinery. However, most studies about LLPS are based on overexpression of core proteins, which is far away from nature condition of cells, whether miRISC underwent LLPS under biological condition remains unknown. Taking miR-490-3p and its target CDK1 as an example, we revealed without overexpression of any protein components, miRISC functioned in an LLPS-depend manner. We firstly found miRISC has liquid-like properties in colon cancer (CC) cells and could fulfill common LLPS criteria under overexpression condition. Then, RIP was performed to confirm miR-490-3p is actually functioning in miRISC. RT-qPCR, western blot and luciferase assays were performed and found miR-490-3p could significantly decrease expression of CDK1 in both RNA and protein levels. However, without overexpression of miRISC components, when treating CC cells with 1,6-hexanediol(1,6-HD), a widely used LLPS inhibitor, the silence effects of miR-490-3p to CDK1 were totally abolished, no matter in RNA, protein or luciferase levels, suggesting that miRISC functions in an LLPS-depend way under biological condition. In conclusion, we found miR-490-3p could silence CDK1 to inhibit the proliferation of CC cells in an LLPS-depend manner.